INTEGRATING ARTIFICIAL INTELLIGENCE IN HRM: THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN ENHANCING DECISION-MAKING PROCESSES - Ashrafuzzaman, Md; Prince, Khan Bahadur; Rahman, Anisur (International Journal of Management Information Systems and Data Science, 2024)
This study delves into the integration of Artificial Intelligence (AI) in Human Resource Management (HRM) and examines the pivotal role of Management Information Systems (MIS) in enhancing decision-making processes. The transformative capabilities of AI are revolutionizing HRM by making operations more efficient, precise, and data-driven. By leveraging AI, MIS can significantly improve the decision-making processes within HRM, enabling more accurate, timely, and objective outcomes. This comprehensive analysis, based on a systematic review of 100 studies, underscores the various benefits of integrating AI within HRM systems, such as improved recruitment processes, enhanced performance management, and increased employee engagement. Additionally, the study addresses the challenges associated with AI adoption, including technical, ethical, and organizational hurdles. It also explores the future prospects of AI in HRM, suggesting that continuous advancements and strategic implementations of AI-enabled MIS can lead to superior organizational outcomes. The findings from this study indicate that the adoption of AI-enabled MIS holds substantial potential for enhancing HR decision-making processes, ultimately contributing to better organizational performance and competitive advantage.